Current status and future tends of combined process producing acetone and phenol. 1. The market review and modern state phenol preparation processes. - E. A. Ananieva; E. V. Egorova; L. B. Larin (Тонкие химические технологии, 2007)
The combined preparation of phenol and acetone from cumol is one of the large-scale production processes of general organic synthesis. Accordingly increasing requirements of isopropylbenzene hydroperoxid as the raw material for the preparation of phenol and acetone and as the individual product, leads to constant development of effective methods of improving process with aim to minimize energy expenses and resources costs. The review of consumption market, phenol production, dynamic of the average product cost is described and the main directions and volumes of cargo are performed.